Risk factors for diabetic autonomic cardiovascular neuropathy in children and adolescents with type 1 diabetes mellitus - Maria Rustemovna Shaidullina; Farida Vadutovna Valeeva; Eduard Zakirzyanovich Yakupov (Сахарный диабет, 2013)
Aim. To determine risk factors for diabetic autonomic cardiovascular neuropathy (DACN) and to optimize diagnostic procedures for children and adolescents with type 1 diabetes mellitus. Materials and methods. Heart rate variability (HRV) was assessed in 101 subjects with type 1 diabetes mellitus aged 5?17 y.o. in 4 functional tests. Subjects with 3 positive tests out 4 were considered positive for DACN. Results. Increased glycemic variability (9+ mmol/l per day), regular hypoglycemic events and late diabetes complications were found to be DACN risk factors in children and adolescents. Conclusions. A diagnostic algorithm for DACN in children and adolescents with type 1 diabetes mellitus based on orthostatic HRV variability assessment shows high sensitivity and efficiency.